KEEFEKTIFAN TEPUNG BIJI PINANG (Areca catechu L.) TERHADAP MORTALITAS HAMA KUMBANG BUBUK BERAS (Sitophilus oryzae L.) DI PENYIMPANAN - Desita Salbiah; Melani Fitriana (UIR Press, 2025)
Rice is the staple food of the Indonesian population. The decline in rice quality is caused by the attack of plant pests during storage, particularly Sitophilus oryzae L. A recommended control method is the use of plant-based insecticide, namely areca nut (Areca catechu L.) seed powder. This research aims to determine the effective dose of areca nut seed powder (A. catechu L.) for controlling rice weevil (S. oryzae L.) mortality during storage. The research was conducted at the Plant Pest Laboratory of the Faculty of Agriculture at Riau University from November 2024 to January 2025. The study was conducted experimentally using a completely randomized design with five treatments and four replications. The study consisted of two series: the first included 20 experimental units to observe initial mortality time, lethal time 50, daily mortality, and total mortality, while the second included 20 experimental units to observe population growth and rice weight loss. The doses of areca nut seed powder used for each experimental unit were 0 g.100 , 2.5 g.100 , 5 g.100 , 7.5 g.100 , and 10 g.100 . Data were analyzed statistically using the DMRT test at the 5% level. The results showed that a dose of 10 g.100 rice was the most effective for controlling S. oryzae, causing a total mortality of 82.5% with an initial mortality time of 28.25 hours after application and a lethal time 50 of 169.5 hours. It resulted in the lowest percentage of rice weight loss at 0.95% and the lowest increase in insect population, with only 3.25 individuals.